Pemanfaatan TIK Oleh UMKM Terhadap Peningkatan Ekonomi Pada Masa Covid-19 Di Kabupaten Jember - Mutmainnah (LAN TABUR : Jurnal Ekonomi Syariah, 2022)
The COVID-19 pandemic has changed the way people live in terms of health and the economy. The economic sector, especially MSMEs, is the sector that has most felt the impact of the Covid 19 pandemic, due to the limited use of digital technology, this of course affects the level of the Indonesian economy. The area in Indonesia that ranks third highest based on the number of MSMEs in East Java is Jember Regency. The purpose of this study is to provide an overview of the use of ICT by SMEs, the economic level of SMEs and the relationship between the use of ICT and economic improvement of SMEs in Jember. This research method is a quantitative method with a descriptive approach. Collecting data through sending survey links to MSME associations in Jember. The data was analyzed using the SPSS 2019 application with simple linear regression analysis. The general conclusion is that SMEs in Jember Regency use 1-10 ICT, including cellphones, laptops, computers, sound systems and printers. The most widely used supporting applications are Whatsapp, Instagram, Facebook, Twitter, and Warung Buku. SMEs in Jember Regency have an average income of 29 million - 30 million per month. The income level of MSMEs in Jember Regency is included in very high income. The use of ICT by MSMEs has a significant effect on economic improvement in Jember Regency, as shown by the tcount value of 9.420 with a significance value of 0.000 <0.05.